Effect of CO2 laser power intensity on the surface morphology and friction behavior of alumina ceramic brackets. Issue 8 (3rd May 2017) - Rabiee, Sayed Mahmood; Eftekhari, Seyedeh Zeinab; Arash, Valiollah; Amozegar, Nadereh; Fathi, Alireza; Tavanafar, Saeid; Bijani, Ali
Abstract: Objective: This study aims at reducing frictional resistance of the ceramic brackets by using CO2 laser irradiation. Methods: Forty‐two polycrystalline Al2 O3 ceramic brackets were randomly divided into six groups of seven samples: a control group B0 (not subjected to laser irradiation) and five groups subjected to irradiation with intensities of 10 (B10), 30 (B30), 70 (B70), 90 (B90), and 110 (B110) J/cm 2 . After irradiation, two samples from each group were evaluated by scanning electron microscopy (SEM) and atomic force microscopy (AFM), while the remaining five samples were tested for frictional resistance. The sliding friction of stainless steel wires (SS‐wires) in the brackets was measured using a universal testing machine. Results: Samples from the first set (groups B0, B10, and B30) were significantly more resistant to wire sliding than the samples from the second set (groups B70, B90, and B110). The SEM analysis shows different degrees of blister formation on the bracket surfaces subjected to laser irradiation and no changes in their grain sizes. The AFM results indicate more consistent blister formation for groups B70, B90, and B110 than for other groups. Conclusion: Different CO2 laser power intensities significantly affect frictional resistances of SS‐wires in Al2 O3 ceramic brackets. Abstract : This is the first study using a CO2 laser to reduce frictional resistance between ceramic brackets and SS‐wires. CO2 laser irradiation of 70, 90, and 110 j/cm 2 reduced the sliding friction. SEM and AFM showed change in surface morphology of brackets.